Web services-soup to nuts simplified web services development using visual tools. - Cavanaugh, Erin (SOA webservices journal.)
When you set out to develop a new Web service, do you start banging out angle brackets right off the bat, or do you sketch out the logic of your service first? For most engineers, the graphical approach to implementing business logic is much more accessible. Only after a picture is created does the complexity of translating it into code come into play.